2009
DOI: 10.1016/j.jcin.2008.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Biodegradable Polymer-Coated Sirolimus-Eluting Stents in “Real-World” Practice

Abstract: This multicenter registry documents satisfactory safety and efficacy profiles, as evidenced by low rates of major adverse cardiac events and stent thrombosis up to 18 months, for the Excel biodegradable polymer-based sirolimus-eluting stent when used with 6 months of dual antiplatelet therapy in a "real-world" setting. (Multi-Center Registry Trial of EXCEL Biodegradable Polymer Drug-Eluting Stent [CREATE]; NCT00331578).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 36 publications
4
35
0
2
Order By: Relevance
“…The stents' clinical effectiveness and safety was initially demonstrated in the 100-patient SERIES I (Study on the Supralimus ® Sirolimus-Eluting Stent in the Treatment of Patients With Real World Coronary Artery Lesions) First-in-Man study, which reported a rate of in-stent angiographic restenosis of 0.0% and a late loss of 0.09 ± 0.37 mm at 6-months of follow-up. At 30 months, the rate of target vessel revascularisation (TVR) was 4%, with no reported definite ST [27]. Similar clinical effectiveness and safety have been reported at 6-months of follow-up in the larger e-SERIES multicenter registry, which included over 1,100 patients [28].…”
Section: Discussionmentioning
confidence: 58%
“…The stents' clinical effectiveness and safety was initially demonstrated in the 100-patient SERIES I (Study on the Supralimus ® Sirolimus-Eluting Stent in the Treatment of Patients With Real World Coronary Artery Lesions) First-in-Man study, which reported a rate of in-stent angiographic restenosis of 0.0% and a late loss of 0.09 ± 0.37 mm at 6-months of follow-up. At 30 months, the rate of target vessel revascularisation (TVR) was 4%, with no reported definite ST [27]. Similar clinical effectiveness and safety have been reported at 6-months of follow-up in the larger e-SERIES multicenter registry, which included over 1,100 patients [28].…”
Section: Discussionmentioning
confidence: 58%
“…The Excel stent is a sirolimus-eluting stent (SES) coated with a biodegradable polylactic acid (PLA) polymer and its feature has been described elsewhere [12]. The PLA polymer resorption is complete in the porcine model by 6 to 9 months, thus leaving only the bare-metal platform in perpetuity.…”
Section: Methodsmentioning
confidence: 99%
“…The safety and efficacy of these devices have been assessed clinically in first in man (FIM) and observational studies [30][31][32] . For example, in the Paclitaxel In Stent Controlled Elution Study, the pharmacokinetics of the DES and not dose of the immunosuppressive agent appears to be associated with neointimal suppression and clinical outcome [30] .…”
Section: Technologymentioning
confidence: 99%